Are carfentanil and acrylfentanyl naloxone resistant? - Feasel, Michael G.; Moran, Theodore S.; Cheng, Boyle C.; Averick, Saadyah (Frontiers in Psychiatry, 2024)
The rapid rise in deaths since 2012 due to opioid poisoning is correlated with the proliferation of potent synthetic opioid agonists such as fentanyl, acrylfentanyl, and carfentanil. The efficacy of frontline antidotes such as naloxone in reversing such poisoning events has been questioned, and the possibility of naloxone-resistant synthetic opioids has been raised. In this manuscript, we applied in vitro techniques to establish the median effective inhibitory concentrations for fentanyl, acrylfentanyl, and carfentanil and subsequently evaluate naloxone’s ability to reverse agonist–receptor interactions.